Doramectin Induces Apoptosis in B16 Melanoma Cells - Crotts, Megan S.; Jacobs, Jena C.; Baer, Robert W.; Cox, James L. (Anti-Cancer Agents in Medicinal Chemistry, 2025)
Introduction/ObjectiveMetastatic melanoma resists current pharmacological regimens that act through apoptosis. This indicates that therapies acting via non-apoptotic cell-death pathways could be pursued. Doramectin has shown promising results in another cancer of neural crest origin, neuroblastoma, through the inhibition of growth via autophagy. Our research hypothesis is that doramectin induces autophagy in B16F10 melanoma cells.MethodsCells were treated with doramectin (15 uM) or a combination of both doramectin and a cell-death inhibitor, compared to untreated control cells (media), and then analyzed with MTT analysis. Likewise, MDC analysis was completed to detect autophagy involvement with doramectin treatment. Flow cytometry and TUNEL Assay were conducted to observe cell death-related effects.ResultsMTT analysis of doramectin-treated cells displayed a decrease in cell growth compared to control. Apoptotic morphology was prominent in melanoma cells treated with doramectin. Increased autophagy was not detected by fluorometric microscopic analysis. Flow cytometry analysis of doramectin-treated cells showed apoptosis as a major mode of cell death with some necrosis.ConclusionDoramectin induces a novel cell-death mechanism in melanoma compared to other forms of cancer and should be studied as an effective anti-cancer agent for melanoma treatment.
Keywords: autophagy